Preventive Policy Strategy for Banking the Unbanked: Savings Accounts for Teenagers?. Issue 1 (2nd January 2016) - Friedline, Terri; Despard, Mathieu; Chowa, Gina A. N.
Abstract : Concern over percentages of unbanked and underbanked households in the United States and their lack of connectedness to the financial mainstream has led to policy strategies geared toward reaching these households. Using nationally-representative longitudinal data, a preventive strategy for banking households is tested that asks whether young adults are more likely to be banked and own a diversity of financial assets when they are connected to the financial mainstream as teenagers. Young adults are more likely to own checking accounts, savings accounts, certificates of deposit, and stocks when they had savings accounts as teenagers. Policy implications are discussed.